2017
DOI: 10.1016/j.automatica.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of infinite dimensional port-Hamiltonian systems by nonlinear dynamic boundary control

Abstract: The conditions for existence of solutions and stability, asymptotic and exponential, of a large class of boundary controlled systems on a 1D spatial domain subject to non-linear dynamic boundary actuation are given. The consideration of such class of control systems is motivated by the use of actuators and sensors with non linear behaviour in many engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…Linear static and dynamic output feedback has been studied by Villegas. Related results for nonlinear dynamic output feedback were obtained in Ramirez et al [27] Here we only mention the following results for impedance passive port-Hamiltonian systems. Augner [23] extended these results for nonlinear static and dynamic output feedback.…”
Section: Stabilizability By Output Feedbackmentioning
confidence: 56%
See 1 more Smart Citation
“…Linear static and dynamic output feedback has been studied by Villegas. Related results for nonlinear dynamic output feedback were obtained in Ramirez et al [27] Here we only mention the following results for impedance passive port-Hamiltonian systems. Augner [23] extended these results for nonlinear static and dynamic output feedback.…”
Section: Stabilizability By Output Feedbackmentioning
confidence: 56%
“…Boundary control and observation systems satisfying (27) are called scattering passive. We now return to the port-Hamiltonian system (4).…”
Section: Port-hamiltonian Systems With Boundary Control and Observationmentioning
confidence: 99%
“…In [11] it is shown that the port-Hamiltonian system (16), (18) In this paper we have studied the notion of exact controllability for a class of linear port-Hamiltonian system on a one dimensional spacial domain with full boundary control and no internal damping. We showed that for this class wellposedness implies exact controllability.…”
Section: Example Of An Exactly Controllable Port-hamiltonian Systemmentioning
confidence: 99%
“…Here we follow the functional analytic point of view. This approach has been successfully used to derive simple verifiable conditions for well-posedness [13,10,9,1,11,14], stability [1,15] and stabilization [16,17,15,18] and robust regulation [19]. For example, the port-Hamiltonian system (1) Provided the port-Hamiltonian system (1) is well-posed, we aim to characterize exact controllability.…”
mentioning
confidence: 99%
“…It has been initially introduced for finite dimensional nonlinear systems described by ODEs [13,14], and then generalized to infinite dimensional systems described by partial differential equations (PDEs) in more recent years [15][16][17]. This provides a standardized framework for control design, especially suited for energy based control strategies both for finite dimensional [18,19] and infinite dimensional systems [20,21]. The PH modelling allows to express a system as the composition of different elements that exchange energy in a power preserving way.…”
Section: Introductionmentioning
confidence: 99%